2018
DOI: 10.1107/s1600577518005143
|View full text |Cite
|
Sign up to set email alerts
|

Thickness-dependent structural characteristics for a sputtering-deposited chromium monolayer and Cr/C and Cr/Sc multilayers

Abstract: The interior structure, morphology and ligand surrounding of a sputtering-deposited chromium monolayer and Cr/C and Cr/Sc multilayers are determined by various hard X-ray techniques in order to reveal the growth characteristics of Cr-based thin films. A Cr monolayer presents a three-stage growth mode with sudden changes occurring at a layer thickness of ∼2 nm and beyond 6 nm. Cr-based multilayers are proven to have denser structures due to interfacial diffusion and layer growth mode. Cr/C and Cr/Sc multilayers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
(18 reference statements)
1
3
0
Order By: Relevance
“…The data imply that the contrast between the C and Cr nanolayers and the density of the Cr nanolayers decreased as the Cr deposition power (and thereby, its thickness) decreased. A direct relationship between the density and thickness of Cr nanolayers has been reported in a previous research as well (25). These conclusions can be verified by the HR-TEM analysis also, as discussed earlier.…”
Section: Tailoring Of the Nanointerfaces: Growth Mode And Intermixingsupporting
confidence: 83%
See 1 more Smart Citation
“…The data imply that the contrast between the C and Cr nanolayers and the density of the Cr nanolayers decreased as the Cr deposition power (and thereby, its thickness) decreased. A direct relationship between the density and thickness of Cr nanolayers has been reported in a previous research as well (25). These conclusions can be verified by the HR-TEM analysis also, as discussed earlier.…”
Section: Tailoring Of the Nanointerfaces: Growth Mode And Intermixingsupporting
confidence: 83%
“…Cr is used frequently in carbon-based systems either as a sublayer (strong adhesion to steel materials) or an interlayer (because it displays zero or low intermixing with carbon) (24). According to a previous study, Cr can potentially grow in FM mode when combined with carbon (25). This enables the formation of atomically thick, continuous Cr layers in a DLC medium, which is essential for the design of nanolayered coatings as discussed earlier.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that adjusting the pressure in the deposition step can significantly reduce the interface roughness in Mo/Si PMMs [45]. In addition, the roughness is also affected by the thickness of individual layers [46]. Thus, these factors should be considered simultaneously.…”
Section: Structural and Optical Propertiesmentioning
confidence: 99%
“…It was shown that adjusting the pressure in the deposition step can significantly reduce the interface roughness in Mo/Si PMMs [45]. On the other hand, the roughness is also affected by the thickness of individual layers [46]. Thus, these factors should be considered simultaneously.…”
Section: Structural and Optical Propertiesmentioning
confidence: 99%